Push Up Development Test Instruments Based On Sensor Technology - Hartati Hartati; Sri Sumarni; M.Ageng Aidil Ramdhon (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2020)
This study aims to develop a sensor technology-based push up test instrument for Sriwijaya State Sports School students. The research method used is research and development (research and development). Development research subjects were divided into two groups. Small-scale group trials consist of 10 students and large-scale group trials consist of 21 students. The results showed that the sensor technology-based push-up test instrument had a 94% validity test and sports measurement expert level and an IT expert validity of 75% so that the tool could be said to be feasible. The level of reliability in trials of small groups of men amounted to 0.994 and small groups of women amounted to 0.988 with the High category. Whereas the large group of male trials was 0.998 and the large group of women was 0.946 with the High category so it was said that the level of tool reliability was carried out in the large group and small group trials having the High reliability category. The implication of this research is that the development of sensor technology-based push up test instruments can be used as a valid, effective, and practical push up measurement tool.